Assessment of the effects of using the cooperative learning pedagogy in a hybrid mechanics of materials course. Issue 3 (July 2019) - Ahn, Benjamin; Nelson, Matthew
Literature shows that the cooperative learning pedagogy increases engineering students' performance in a traditional lecture-based course. This study investigated whether a similar positive effect on student performances would be found in a hybrid course that implemented the cooperative learning pedagogy. To examine this question, this study compared the performance of engineering students taught with and without the cooperative learning pedagogy in a sophomore-level Mechanics of Materials course that implemented the hybrid format. The study findings showed that cooperative learning offered no additional increase in performance for students. Student characteristics (e.g. gender, class load in the semester, attendance, previous GPA) did not influence this finding. However, many students reported that they enjoyed working in teams, preferred including the cooperative learning pedagogy in hybrid courses and suggested that similar engineering courses be taught using the cooperative learning pedagogy.